(untitled) (Revista de História Regional, 2024)
In this text, we analyze the expansion movement of coffee farming in the Southwest of Minas Gerais – municipalities of Guaxupé, Guaranésia and Muzambinho – between the years 1869 and 1920. Using a diverse set of sources – internal farm records, formation deeds of crops, post-mortem inventories and reports from Companhia Mogyana de Estradas de Ferro – we seek to describe the process of setting up regional coffee farming. Firstly, we analyzed the first expansion of coffee plantations in the area between the final decades of the Empire and the first years of the 20th century. Secondly, we discuss the impacts of the arrival of the railway on the regional economy and the consolidation of the region as an important coffee center. Keywords: Southwest of Minas Gerais, coffee economy, railways.